1997
DOI: 10.1073/pnas.94.25.14077
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-dependent sexual differentiation of dopaminergic neurons in the preoptic region of the mouse

Abstract: Although it has been known for some time that estrogen exerts a profound inf luence on brain development a definitive demonstration of the role of the classical estrogen receptor (ER␣) in sexual differentiation has remained elusive. In the present study we used a sexually dimorphic population of dopaminergic neurons in the anteroventral periventricular nucleus of the hypothalamus (AVPV) to test the dependence of sexual differentiation on a functional ER␣ by comparing the number of tyrosine hydroxylase (TH)-imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
142
0
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(156 citation statements)
references
References 48 publications
11
142
0
3
Order By: Relevance
“…ATD increased the number of TH-immunoreactive neurons in males such that a sex difference no longer existed. These data are similar to those from other rodents, which suggest that neonatal ER activation is necessary for sex differences in periventricular TH expression (Bodo et al, 2006;Simerly et al, 1997). Furthermore, they complement previous data from our lab showing that neonatal estradiol masculinizes TH expression in female prairie voles (Lansing and Lonstein, 2006).…”
supporting
confidence: 89%
“…ATD increased the number of TH-immunoreactive neurons in males such that a sex difference no longer existed. These data are similar to those from other rodents, which suggest that neonatal ER activation is necessary for sex differences in periventricular TH expression (Bodo et al, 2006;Simerly et al, 1997). Furthermore, they complement previous data from our lab showing that neonatal estradiol masculinizes TH expression in female prairie voles (Lansing and Lonstein, 2006).…”
supporting
confidence: 89%
“…Although sex differences in overall neuron number in the BNSTp have not yet been reported for mice, the cluster of androgen receptor-expressing neurons is larger in male mice than in females (27). In AVPV, overall cell density is greater in female mice than in males (5,25) and, as in rats, female mice possess about three times as many dopaminergic neurons in AVPV as do males (28). We reasoned that if Bax is essential for cell death in the BNSTp and AVPV, then sex differences in neuron number might be reduced or eliminated in Bax knockout mice.…”
mentioning
confidence: 86%
“…Previous studies have clearly shown that estrogen signaling through ERα (and ERβ) in the perinatal period mediates the sexual differentiation of the AVPV, a region critical for estrogen positive feedback (Bodo et al, 2006;Simerly et al, 1997). In the AVPV, female mice have more tyrosine hydroxylase immunoreactive (TH-ir) neurons than males and ERαKO males display a feminized AVPV.…”
Section: Positive Feedback On Lhmentioning
confidence: 99%